Science in history - Bernal, J. D. (M.I.T. Press, 1954)
J. D. Bernal's monumental work Science in History is the first full-scale attempt to analyze the relationship between science and society throughout history, from the perfection of the first flint hand ax to the construction of the hydrogen bomb. This remarkable study illustrates the impetus given to and the limitations placed upon discovery and invention by pastoral, agricultural, feudal, capitalist, and socialist systems, and conversely the ways in which science has altered economic, social, and political beliefs and practices.Volume 3 is devoted entirely to the twentieth century and the remarkable growth of scientific thought which has occurred in modern times -- from the new sciences of nuclear physics and electronics to discoveries and advances in biology and related fields.